A Case Report: Hyperthrophic Pyloric Stenosis In 2-Months Old Boy - Luthfi Mohd (Science Midwifery, 2021)
Hypertrophic Pyloric Stenosis (HPS) refers to a narrow pylorus with clinical presentation is projectile and non-bilious vomiting. It occurs at the age of 2-8 weeks, with the case ratio between male-female is about 4:1. Ultrasound and barium meal are modalities to make the diagnosis. Reported a case 2-months old boy, who had chief complaint recurrent projectile and non-bilious vomiting. Ultrasound was performed with result thickening of pyloric with 6 mm of diameter. The patient has done pyloromyotomy. Patient suffered from post operative emesis which is still within normal limits and no other complication.